The interplay between mesenchymal stem cells and the immune microenvironment in rotator cuff tendon-to-bone healing: current progress and future directions - Li, Dong; Zou, Yujia; Zhao, Yuanting (Frontiers in Immunology, 2025)
Rotator cuff injuries frequently result in poor tendon-to-bone healing due to the failure to regenerate the native fibrocartilaginous enthesis and the persistence of a dysregulated immune microenvironment. Mesenchymal stem cells (MSCs) have emerged as promising therapeutic agents, not only for their multilineage differentiation potential but also for their potent immunomodulatory functions. Emerging evidence highlights that MSCs engage in bidirectional crosstalk with immune cells such as macrophages, T cells, and NK cells through both paracrine factors and direct cell–cell contact, critically shaping the reparative versus fibrotic outcome of tendon-to-bone healing. This review summarizes the biological mechanisms underlying MSC-mediated tendon-to-bone healing, with a focus on immune modulation. We discuss recent advances in cell-free approaches, biomaterial-assisted delivery systems, and strategies to enhance the local immune milieu. Current challenges—including MSC heterogeneity, variable patient immune responses, and translational barriers—are also addressed. Finally, we highlight future directions such as personalized immunomodulatory therapies, 3D humanized testing models, and AI-based prediction tools aimed at improving clinical outcomes. Specifically, AI algorithms that integrate patient-specific immune profiles—such as single-cell transcriptomics and cytokine signatures—may enable responder stratification and guide individualized MSC-based interventions. Understanding and leveraging the MSC–immune interaction is key to unlocking the full potential of regenerative therapies in rotator cuff repair.